PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra, I Gede Cahyadi; Kepramareni, Putu; Manuari, Ida Ayu Ratih; Jayatri, Luh Dwi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
This study aims to determine the effect of institutional ownership, managerial ownership, independent commissioners, return on assets, and current ratio to stock prices in technology companies listed on the ratio on the share price of technology companies listed on the Indonesia Stock Exchange. Indonesia Stock Exchange. This research is a quantitative type research. The data collection method uses purposive sampling method with several predetermined criteria that have been determined. The analytical tool used to test the hypothesis is multiple linear analysis. The results showed that institutional ownership and return on assets have a positive effect on stock prices in technology companies listed on the Stock Exchange. on stock prices in technology companies listed on the Indonesia Stock Exchange for the period 2020-2022. Indonesia Stock Exchange for the period 2020-2022. Meanwhile, managerial ownership, independent commissioners, and current ratio have no effect on stock prices in technology companies listed on the Indonesia Stock Exchange for the period 2020-2022. on technology companies listed on the Indonesia Stock Exchange for the period 2020-2022.